Decentralisation and Social Services in England - Walter Lorenz (Social Work and Society)
Although Great Britain is not normally credited with the achievement of having been the first nation state to implement measures characteristic of a welfare state (this honour goes to Germany and Bismarck's strategy of promoting social insurance in the 1880s) it nevertheless pioneered many models of welfare services in view of the early onset of industrialisation in that country and the subsequent social problems it created. Organisations like the Mutual Insurance and Friendly Societies, the Charity Organisation Society or the Settlement Movement characterised an early approach to welfare that is based on initiatives at the civil society level and express a sense of self-help or of self-organisation in such a way that it did not involve the state directly. The state, traditionally, dealt with matters of discipline and public order, and for this reason institutions like prisons and workhouses represented the other end of the scale of 'welfare' provisions.